Epilepsy and behavioral changes, type 1 diabetes mellitus and a high titer of glutamic acid decarboxylase antibodies. Issue 8 (29th December 2015) - Ganelin‐Cohen, Esther; Modan‐Moses, Dalit; Hemi, Rina; Kanety, Hannah; Ben‐zeev, Bruria; Hampe, Christiane S.
Abstract : Autoantibodies to the 65 kDa isoform of glutamate acid decarboxylase (GAD65Ab) are associated with a range of clinical disorders, including type 1 diabetes (T1D) and stiff‐person syndrome (SPS). In this article we describe a young girl who was diagnosed with T1D at the end of her first year of life and developed drug‐resistant epilepsy 18 months later, followed by behavioral disturbances. She was admitted to our center at the age of 5 yr, at which time high GAD65Ab titers were detected in the patient's serum and cerebrospinal fluid (CSF). The titer remained elevated during 19 months of follow‐up. Furthermore, GAD65Ab in both serum and CSF showed epitope binding characteristics similar to those observed for GAD65Ab in SPS patients, and GAD65Ab in the serum reduced GAD65 enzyme activity. Our results suggest an association between high GAD65Ab titers and epilepsy in children with T1D. Careful titration and characterization of GAD65Ab regarding inhibition of enzyme activity and epitope specificity may be helpful in identifying T1D patients at risk for neurological complications.